Produção científica sobre estudos métricos da informação: uma análise dos artigos inseridos na base de dados LISA no período de 2013 - 2014, sob a ótica da Lei de Bradford - CARDOSO, Thaís dos Santos (2021)
Metric studies are the main techniques for measuring information with objective of measure the amount of scientific information. In this context, the objective of this research is to analyze the characteristics of the articles that approach the proposed theme and its subdisciplines (Bibliometrics, Webometrics, Scientometrics, Informetrics, Altmetrics). The research has bibliographic character, its classification is quantitative. An analysis of the articles published in the period from 2013 to 2014 was made, the LI SA database was used as the search tool for being the most complete in the area of Information Science. Articles were analyzed using Bradford's Law determined the productivity of journal's. Of the articles indexed in the database, 87 articles were retrie ved in the period of 2013 2014 that dealt with the subject, 36 periodicals responsible for the publication of articles.